Variations in lengths of stay and rates of day case surgery: implications for the efficiency of surgical management. Issue 2 (June 1990) - Morgan, M; Beech, R
Abstract : Variability in lengths of acute hospital stay and rates of day case surgery is shown to be a continuing pattern which occurs both between and within countries. A model of the determinants of health service activity is presented and the contribution of different factors to the observed variations is assessed. Differences in methods of funding health services are identified as a major determinant of the between country variations, while the within country variations largely reflect the influence of local differences in facilities and services and the organisation of care at a hospital level, as well as the independent effects of differences in clinical practice style. The main rationale for advocating a reduction in length of stay and increased use of day surgery is to increase efficiency by reducing costs per case while maintaining the quality of care. These criteria of costs, clinical outcomes and patient acceptability are examined in relation to day case surgery for an intermediate surgical procedure (inguinal hernia repair) and short stay surgery for cholecystectomy. The precise cost savings are shown to depend on the methods of costing, assumptions made and facilities employed, while factors influencing the outcomes achieved include the criteria of patient selection, the surgical techniques employed, and the adequacy of preoperative communication. Barriers to the more widespread adoption of short stay and day case surgery include practical and organisational constraints on clinical practice at a hospital level, lack of awareness among clinicians as to how far their practices differ from current norms, and clinical barriers raised by surgeons who do not see short stay policies as advantageous. Mechanisms to promote changes in clinical practice styles include independent professional audit, peer review, and involvement of clinicians in budgeting and resource allocation. Assessing quality requires that attention is given to patient acceptability and satisfaction as well as to the monitoring of clinical outcomes.